DARI MODERNITAS HINGGA POLIGAMI : PEMIKIRAN ANI IDRUS - Suriani Suriani (HUMANISMA : Journal of Gender Studies, 2018)
The opportunity to get education for Indonesian women in the early 20th century had an impact on increasing women's activities in the fields of press, social, economic and political. Women with their thoughts present provide their own color in various aspects of life at that time. One of these women is Ani Idrus. By her writings, she conveyed about life modernity and problems faced by Indonesian women in Dutch colonial period which still exist today. Terbukanya kesempatan untuk mendapatkan pendidikan bagi perempuan Indonesia pada awal abad 20 berdampak pada peningkatan aktivitas perempuan dalam bidang pers, sosial, ekonomi dan politik. Perempuan dengan pemikirannya hadir memberikan warna tersendiri dalam berbagai aspek kehidupan saat itu. Salah satu perempuan tersebut adalah Ani Idrus. Melalui tulisannya, ia menyampaikan tentang modernitas dan persoalan-persoalan hidup yang dihadapi perempuan Indonesia pada masa kolonial Belanda yang masih juga ada hingga saat ini.